Manuel González Prada, modernista poet - Ward, Thomas (2022)
This article argues that the poet and essayist Manuel González Prada is part of the literary school called modernism and examines three aspects of the situation: 1) the exclusion of González Prada from international criticism; 2) the appearance of modernism in Peru and the role of González Prada and especially Clorinda Matto de turner in it; and 3) a comparison of some modernist elements in the poetry of González Prada and Rubén Darío.